(untitled) (Revista Electrónica REDINE, 2018)
To determine the level of knowledge of mothers of preterm newborns on the care it deserves to its discharge from the Neonatal Pathology Service, Central Hospital "Antonio Maria Pineda", we conducted a descriptive study, selecting 63 mothers of infants hospitalized , who were administered the survey conducted, obtaining: 96.86% considered breastfeeding as enough to feed his baby, while 87.30% would use it exclusively, 7.94% and whole milk also administer rice water and 4.76% the food with artificial formula. About the position to sleep, 38.10% said the ideal position is the left lateral position. 61% would start the bath after the fall of the umbilical stump, with diverse opinions on the product to use. By controlling the temperature, 58.73% would use the thermometer rectal and axillary thermometer 12.6%, a similar percentage would only do by touch. 47% only recommends frequent hand washing to prevent infection. Although only 50% knew the immunization schedule, 88% admitted that require special vaccine All agree that the cure must be umbilical with absolute alcohol daily. Considering the results, is necessary to implement institutional measures to inform mothers about the care it deserves preterm infants at discharge.